1998
DOI: 10.1101/gad.12.16.2510
|View full text |Cite
|
Sign up to set email alerts
|

Activated transcription independent of the RNA polymerase II holoenzyme in budding yeast

Abstract: We investigated whether the multisubunit holoenzyme complex of RNA polymerase II (Pol II) and mediator is universally required for transcription in budding yeast. ⌬CTD Pol II lacking the carboxy-terminal domain of the large subunit cannot assemble with mediator but can still transcribe the CUP1 gene. CUP1 transcripts made by ⌬CTD Pol II initiated correctly and some extended past the normal poly(A) site yielding a novel dicistronic mRNA. Most CUP1 transcripts made by ⌬CTD Pol II were degraded but could be stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
70
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 61 publications
11
70
0
Order By: Relevance
“…Our observation is in line with previous results that showed that Cdk9p, the main CTD Ser-2 kinase, is critical for 3Ј-end processing of mRNAs, but less so for Pol II transcription (25,26). In addition, we demonstrate that the expression of a small portion of the yeast genome is Kin28p-independent, which expands our previous observation (27,28).…”
Section: Discussionsupporting
confidence: 82%
“…Our observation is in line with previous results that showed that Cdk9p, the main CTD Ser-2 kinase, is critical for 3Ј-end processing of mRNAs, but less so for Pol II transcription (25,26). In addition, we demonstrate that the expression of a small portion of the yeast genome is Kin28p-independent, which expands our previous observation (27,28).…”
Section: Discussionsupporting
confidence: 82%
“…Expression of heat-shock genes can occur in the absence of kin-28 in yeast (48,49), and phosphorylation of the CTD at heat shock promoters has been observed in the absence of CDK7 in Chironomus tentans (50). Our finding that hsp16-2 is partially resistant to a reduction in cdk-7 activity is consistent with the idea that CDK7 is not required equally at all promoters.…”
Section: Discussionsupporting
confidence: 80%
“…Samples were examined for cell-cycle progression by counting the cells indicated explained simply (see Discussion). Transcript levels of SSA4 and CUP1 were not affected by the overexpression possibly because transcription of both genes is known to be independent of KIN28 (Lee and Lis, 1998;McNeil et al, 1998).…”
Section: Negative Regulation Of Kin28±ccl1 By Srb10mentioning
confidence: 92%